Thresholds for hanger slackening and cable shortening in the Melan equation for suspension bridges. (February 2018) - Gazzola, Filippo; Sperone, Gianmarco
Abstract: The Melan equation for suspension bridges is derived by assuming small displacements of the deck and inextensible hangers. We determine the thresholds for the validity of the Melan equation when the hangers slacken, thereby violating the inextensibility assumption. To this end, we preliminarily study the possible shortening of the cables: it turns out that there is a striking difference between even and odd vibrating modes since the former never shorten the cables. These problems are studied both on beams and plates.